1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Integral involving square root and exp

  1. Mar 2, 2014 #1
    1. The problem statement, all variables and given/known data

    [itex]\int[/itex][itex]\frac{dx}{\sqrt{e^{x} + 1}}[/itex]

    2. Relevant equations
    Using u-substitution

    3. The attempt at a solution

    Let u = [itex]\sqrt{e^{x} + 1}[/itex] [itex]\Rightarrow[/itex] u[itex]^{2} - 1[/itex] = e[itex]^{x}[/itex]
    Then, du = [itex]\frac{e^{x} dx}{2\sqrt{e^{x} + 1}}[/itex] [itex]\Rightarrow[/itex] dx = [itex]\frac{2u du}{u^{2}-1}[/itex]

    So, [itex]\int[/itex][itex]\frac{dx}{\sqrt{e^{x} + 1}}[/itex] = [itex]\int[/itex][itex]\frac{2u du}{u(u^{2}-1)}[/itex]

    But, I'm stuck at this point. I think I want to break it up into two simpler integrals, but I'm not sure how to do this. Any suggestions would be greatly appreciated!
  2. jcsd
  3. Mar 2, 2014 #2


    User Avatar
    Science Advisor
    Homework Helper

    Partial fractions is what you want. Factor the denominator.
  4. Mar 2, 2014 #3

    So, [itex]\int[/itex][itex]\frac{dx}{\sqrt{e^{x} + 1}}[/itex] = [itex]\int[/itex][itex]\frac{2u du}{u(u^{2}-1)}[/itex] = [itex]\int[/itex][itex]\frac{2du}{(u+1)(u-1)}[/itex]

    And now I'm stuck again.
  5. Mar 2, 2014 #4


    User Avatar
    Science Advisor
    Homework Helper

    Partial fractions! ##\frac{1}{(u+1)(u-1)}=\frac{A}{u+1}+\frac{B}{u-1}## for some constants A and B. Find those constants.
  6. Mar 2, 2014 #5
    Okay. I think I've got it.

    So, [itex]\int[/itex][itex]\frac{dx}{\sqrt{e^{x} + 1}}[/itex] = [itex]\int[/itex][itex]\frac{2u du}{u(u^{2}-1)}[/itex] = [itex]\int[/itex][itex]\frac{2du}{(u+1)(u-1)}[/itex] = [itex]\int[/itex][itex]\frac{du}{u-1}[/itex] - [itex]\int[/itex][itex]\frac{du}{u-1}[/itex] = ln|u-1| - ln|u+1| = ln[itex]\frac{|u-1|}{|u+1|}[/itex] where u = [itex]\sqrt{e^{x}+1}[/itex]

    = ln[itex]\frac{\sqrt{e^{x}+1}-1}{\sqrt{e^{x}+1}+1}[/itex]

    Thank you for all your help.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted